Molecular Characterization Of Human Group A Rotavirus Isolates From Malaysia And Development Of A Colorimetric Pcr-Based Test For The Detection Of P[8] Genotype - Hassan, Zuridah (2004)
Rotavirus has been recognized as a leading cause of the diarrhoeal illness in children under 5 years of age in the developing world. Latex agglutination test was used to detect group A rotavirus from 157 in-patients from different hospitals in Malaysia during 2000 to 2001. Diarrhoea was detected in 31 (19.7%) children and majority were under two years of age. When viewed under electron microscope by negative staining, rotavirus was seen as both double-shelled and single-shelled particles. Thirty one rotavirus antigen positive samples with typical group A electropherotype were further characterized into their G or P types by polymerase chain reaction (PCR) assay. The two common electropherotypes were IIC (51.6%) and IIG (35.5%). The most prevalent VP4 genotype was 25 (80.6%) P[8] and 1 (3.2 %) P[6]. Genotype P[4] and P[9] were not isolated and 5 (16.1 %) were P untypable (PUT). Regarding the VP7 genotype, G4 was the most prevalent (64.5 %), followed by G1 (6.45%), G2 (6.45%) and G3 (3.2 %). Neither G8 nor G9 was found and 6 (19.4 %) were G untypable (GUT). Studies in many countries found that G1P[8], G4P[8], G2P[4] and G3P[8] are the group A rotavirus strains more commonly seen in children. However from this present study, the common strains in Malaysia were G4P[8], G1P[8] and G3P[8]. One GUTP[6] strain (designated as 7W) was identified for the first time in Kuala Lumpur. Restriction endonuclease HaeIII and Sau96I were also used to characterize the VP7 gene of the local 7W strain. However a restriction profile could not be assigned. The P[8] and P[6] local strains (represented by 67F and 7W, respectively) were also characterized by nucleotide sequence analysis. Phylogenetic analysis revealed that the VP4 genes of the 67F and 7W formed a distinct lineage. The P[8] and P[6] are encoded by distinct VP4 gene alleles. The main diagnostic problem is the genetic diversity of these alleles among different rotavirus strains. To overcome this problem, a method that employs non-radioactive dot hybridization was successfully developed for P[8] and P[6]. VP4 cDNA rotavirus-specific probes were prepared and labelled with digoxigenin (DIG). Anti-DIG-alkaline phosphatase and the substrate NBT/BCIP were used to detect the binding of the probe to target sequence. A simple, practical, sensitive and specific assay based on polymerase chain reaction (PCR) and a colorimetric detection method (ELISA) for the typing of rotavirus in infected faeces has been developed succesfully. A set of oligonucleotides was employed for a single-tube reverse-transcription nested PCR (RT-nPCR). Upon synthesis of the first strand cDNA, a first stage of 10 cycles of PCR amplification was run to generate an 876-bp dsDNA from the 5’ terminal third of gene 4. The process was completed in the same tube by performing another 35 cycles of second stage amplification incorporating a biotinylated and digoxigenin 5’-end labelled primers. The RT-nPCR produced a 180-bp amplicon representing the VP4 P[8] type. The sensitivity of the RT-nPCR method was compared to non-nested PCR method and nested PCR was found to be 100 times more sensitive. To further increase the sensitivity, the enzyme-linked immunoassay (ELISA) was incorporated into the system. Streptavidin-coated microtitre plate was used to capture the biotinylated PCR-amplified products. This RT-nPCR ELISA was able to detect RNA as low as 4 pg nucleic acid. It was designed to type the single most epidemiologically important human rotavirus VP4 P[8] type which is often associated with rotavirus G1, G3 and G4 types. Monoclonal antibodies (Mabs) were used for G serotyping, but no Mabs were availabe for P serotyping. Therefore, the RT-nPCR ELISA method is a very useful technique to detect rotavirus.